ABORSI AKIBAT KEHAMILAN YANG TAK DIINGINKAN (KTD): Kontestasi Antara Pro-Live dan Pro-Choice - Wijayati, Mufliha (Analisis: Jurnal Studi Keislaman, 2015)
ABORTION  DUE TO THE UNWANTED  PREGNANCY:  The Contestation between Pro-Live and Pro-Choice. Abortion is one of the classic issues which are always interested  to be debated. The time of the debating  of this abortion  issue is as old as the human life. The polarization  of the differences  of the  point  of view about this topic is the extreme  defense of the interests  to pregnant woman. The abortion due to the unwanted pregnancy is an issue which is resurfaced. This paper will talk about abortion due to the unwanted pregnancy which is not only solely on a legal perspective,  but also in the political  sphere, and social culture. The Utilization  of diverse perspectives is not expected to lead to the  justification unilaterally,  given the  complexity  surrounding the issue of abortion.  The issue of legal, educational,  political, social, and cultural have been moved to minimize the presence of unwanted pregnancies and reduce the rate of abortion, and further reduce  the number of maternal and child mortality  in childbirth